1998
DOI: 10.2105/ajph.88.8.1225
|View full text |Cite
|
Sign up to set email alerts
|

The association of non-insulin-dependent diabetes mellitus with perceived quality of life in a biethnic population: the San Luis Valley Diabetes Study.

Abstract: OBJECTIVES: This study evaluated the association between quality of life and non-insulin-dependent diabetes mellitus (NIDDM) status, and whether this association differs between Hispanics and non-Hispanic Whites. METHODS: Between 1986 and 1989, cross-sectional data on perceived quality of life (PQOL) were collected from 223 persons with NIDDM and 753 non-diabetic subjects. RESULTS: After adjustment, persons with NIDDM rated their PQOL significantly lower than did control subjects. The relationship of diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 35 publications
1
17
4
Order By: Relevance
“…A previous study found that the presence of complications was unrelated to perceived quality of life (Caldwell et al . 1998); however, this finding contradicts the findings of other studies (Glasgow et al ., 1997; Wexler et al ., 2006).…”
Section: Introductioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A previous study found that the presence of complications was unrelated to perceived quality of life (Caldwell et al . 1998); however, this finding contradicts the findings of other studies (Glasgow et al ., 1997; Wexler et al ., 2006).…”
Section: Introductioncontrasting
confidence: 66%
“…In particular, we found that microvascular complications, diabetic neuropathy, PVD, and CHD were strongly correlated with decreased QOL. In contrast to our findings, Caldwell et al . (1998) concluded that the presence of complications was unrelated to perceived QOL.…”
Section: Discussionmentioning
confidence: 99%
“…If replicated, these data may offer one potential pathway for the early detection and possible prevention of secondary mental or physical illness among those with a primary disorder (e.g., prevention of eating disorders through proper management and treatment of diabetes). Given the rising prevalence and the personal and societal costs of Type 2 diabetes in the population (Caldwell et al, 1998;Kokkonen et al, 1997;Larkin, 2001;Sinclair et al, 2000), these data may hold public health import in efforts to identify those at risk for diabetes and to develop effective methods of preventive intervention. …”
Section: Discussionmentioning
confidence: 99%
“…More than 13 million Americans are diagnosed with diabetes yearly, with a growing prevalence (Kokkonen, Lautala, & Salmela, 1997;Larkin, 2001). Diabetes is associated with increased physical morbidity, social and occupational impairment, increased use of health care services, and premature mortality (Caldwell, Baxter, Mitchell, Shetterly, & Hamman, 1998;Sinclair, Bayer, Girling, & Woodhouse, 2000). Although considered to be distinct, the etiology of both Type 1 and Type 2 diabetes is not completely understood nor are the reasons for the rapidly increasing prevalence of diabetes, especially Type 2, over the past 10 years (Kokkonen et al, 1997;Larkin, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…54,55 Although type 2 diabetes is often asymptomatic in its early stages, as it progresses, it frequently results in serious long-term complications [56][57][58] and lower quality of life. [59][60][61] The American Diabetes Association (ADA) treatment guidelines for type 2 diabetes focus on maintenance of glycemic control and screening for and attempting to prevent the onset or progression of complications. 57 Other treatment approaches can include collaboration between health practitioners and patients, 62,63 and disease management, which has been as-sociated with significant reductions in health care cost and use.…”
Section: Diabetesmentioning
confidence: 99%